PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PADA PT ANEKA TATA NIAGA - Hermanto Hermanto; Nora Pitri Nainggolan (Universitas Muhammadiyah Pringsewu, 2020)
The purpose of this study was to determine the effect of service quality and product quality on customer satisfaction at PT Aneka Tata Niaga using slovin sampling technique with a margin of error of 5% of 155 customers so as to produce 112 respondents who are customers at PT Aneka Tata Niaga. Data collection methods are questionnaires. Data quality test in this study uses the validity and reliability test, the classic assumption test and the influence test in this study using multiple linear regression analysis and coefficient of determination analysis (R2), while the hypothesis testing in this study uses (t test) and (F test ) by using SPSS version 23 software program. the results show that service quality has a partially significant effect on customer satisfaction and product quality has a partially significant effect on customer satisfaction, and service quality and product quality together have a significant simultaneous effect on customer satisfaction at PT Various Commerce. Keywords: Service Quality, Product Quality, Customer Satisfaction